A tale of two syn-rifts: New age information and depositional environment interpretation for the North Falkland Basin syn-rift and implications for the rifting of Gondwana - Rory J. Sutton; Gayle E. Plenderleith; Thomas J.H. Dodd; Lorraine P. Field; Ian L. Millar; Dave J. McCarthy; Thomas A. Randles (Gondwana Research, 2026)

Sector expert and public perceptions of greening of grey infrastructure: a case study in Britain’s Ocean City - Jessica R. Allen; Anaëlle J. Lemasson; Melanie J. Bishop; Katherine A. Dafforn; Kate C. Dodds; Mick E. Hanley; Antony M. Knights; Mariana Mayer-Pinto; Abigail McQuatters-Gollop; Maria L. Vozzo; Louise B. Firth (Urban Ecosystems, 2026)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Predictions of southern migration timing in coastal sharks under future ocean warming - Maria H. Manz; Oliver N. Shipley; Robert M. Cerrato; Robert E. Hueter; Alisa L. Newton; John P. Tyminski; Bryan R. Franks; Tobey H. Curtis; Christopher Fischer; Joshua P. Zacharias; Christopher Scott; Keith J. Dunton; et al. (Conservation Biology, 2025)
Projected redistribution of marine species due to ocean warming may undermine current conservation efforts. Yet, there have been few studies on how ocean warming may alter migration timing. Across 5 years of acoustic telemetry data (2018–2022), we determined environmental drivers of southward migration timing for 6 migratory shark species from summer habitats in the Northwest Atlantic Ocean. We then forecasted how migratory timing from 3 regions, between the New England shelf and Mid‐Atlantic Bight, would respond under future sea surface temperatures (SSTs). Photoperiod and SST were strong predictors of southern migration in sharks, but the strength of these effects varied latitudinally. Overall, we found delayed departure dates from summer habitats under future elevated SSTs, indicating prolonged residency in northern habitats (median = ∼12 days). Sandbar sharks ( Carcharhinus plumbeus ) exhibited the largest delay in the onset of southern migrations (median = 29 days), whereas sand tiger sharks ( Carcharias taurus ) and white sharks ( Carcharodon carcharias ) exhibited the smallest delay (median = 1 day). Delays in migration timing of coastal shark species may alter local ecosystem dynamics and challenge current management strategies. These findings illustrate the utility of collaborative data‐sharing networks to expand understanding of broadscale animal movements and contribute to effective species management under a changing climate.

Optimising parent selection in plant breeding: comparing metaheuristic algorithms for genotype building - S. Yadav; S. Dillon; M. McNeil; E. Dinglasan; R. Mago; P. Dodds; L. Hickey; B. J. Hayes (Theoretical and Applied Genetics, 2025)
Stacking desirable haplotypes across the genome to develop superior genotypes has been implemented in several crop species. A major challenge in Optimal Haplotype Selection is identifying a set of parents that collectively contain all desirable haplotypes, a complex combinatorial problem with countless possibilities. In this study, we evaluated the performance of metaheuristic search algorithms (MSAs)—genetic algorithm (GA), differential evolution (DE), particle swarm optimisation (PSO), and simulated annealing (SA) for optimising parent selection under two genotype building (GB) objectives: Optimal Haplotype Selection (OHS) and Optimal Population Value (OPV). Using a diverse wheat population of 583 lines genotyped for 29,972 SNPs, forming 7645 haplotype blocks and phenotyped for stripe rust scores, we assessed each algorithm’s performance across fitness optimisation, convergence speed, and computational efficiency. GA consistently achieved high fitness and rapid convergence, while DE showed robustness but required longer runtime and careful tuning. PSO performed well under the OHS criterion but was less effective for OPV. SA, although computationally lighter, was less consistent in finding optimal solutions. Simulation over 100 breeding cycles showed that OHS outperformed both OPV and GEBV-based selection in long-term genetic gain and diversity retention. OHS maintained heterozygosity and additive variance, which are key for sustainable improvement, while GEBV selection led to early allele fixation. Our findings underscore the potential of GB strategies that prioritise the collective performance of parent sets rather than individual ranking to enhance selection outcomes in genomic-assisted breeding programmes.

Patterns and drivers of landscape and local habitat use by UK Hawfinches (Coccothraustes coccothraustes) during the breeding season and late winter - Will B. Kirby; Andrew J. Stanbury; Philip V. Grice; Anthony V. Cross; Stephen G. Dodd; Vivien Hartwell; Jerry Lewis; David L. Smith; Paul E. Bellamy (Journal of Ornithology, 2025)

Fine-scale residency and temperature-driven habitat selection in a migratory shark species - Thorburn J.; Gagnon É.; Martin J.; Henry L.-A.; Wright P.J.; Dodd J.; James M.; Neat F. (Environmental Biology of Fishes, 2025)
Many marine species exhibit complex and diverse movements that vary across spatial and temporal scales. These movements must be accounted for when designing effective management and conservation efforts. While environmental cues such as temperature and salinity have been shown to influence the movements of mobile species, it is increasingly documented that social factors can also influence space use and population behaviour. Understanding how various factors influence movement enhances our ability to predict the space use of highly dynamic ocean species. Spurdog ( Squalus acanthias ), known for their tendency to aggregate and use of both coastal and oceanic environments, are an ideal model species for studying drivers of movement. To investigate movement and habitat selection in spurdog, we conducted an acoustic telemetry study from June 2016 to July 2017, tagging 51 spurdog in a partially enclosed fjordic sea loch on the west coast of Scotland. The thermal profile of Loch Etive was recorded to complement the movement data. Our study revealed temperature as a pivotal driver of movement and habitat selection in spurdog, with the unique thermal environment of the fjord enabling year-round residency at a previously undocumented spatial scale, suggesting that such habitats may be especially important for mobile marine species. This study demonstrates the importance of understanding environmental influences on space use and movement to develop effective, climate-resilient management strategies for spurdog and other mobile marine species.

The effectiveness of personalised food choice advice tailored to an individual's socio-demographic, cognitive characteristics, and sensory preferences - R.A. Briazu; L. Bell; G.F. Dodd; S. Blackburn; C. Massri; B. Chang; S. Fischaber; A. Kehlbacher; C.M. Williams; L. Methven; R. McCloy (Appetite, 2024)

Healing country together: A seagrass restoration case study from Gathaagudu (Shark Bay) - Elizabeth A. Sinclair; John Statton; Rachel Austin; Martin F. Breed; Richard Cross; Alex Dodd; Amrit Kendrick; Siegfried L. Krauss; Bianca McNeair; Nykita McNeair; Sean McNeair; Marika Oakley; et al. (Ocean & Coastal Management, 2024)

Clopidogrel Is Associated with Reduced Likelihood of Aneurysmal Subarachnoid Hemorrhage: a Multi-Center Matched Retrospective Analysis - Joseph S. Hudson; Kamil W. Nowicki; Brandon Lucke-Wold; Zachary C. Gersey; William S. Dodd; Ali Alattar; David J. McCarthy; Prateek Agarwal; Zain Mehdi; Michael J. Lang; David M. Hasan; Brian L. Hoh; et al. (Translational Stroke Research, 2024)

First evidence of predation on an adult porbeagle equipped with a pop-off satellite archival tag in the Northwest Atlantic - Brooke N. Anderson; Lauren Horstmyer; Kirsty L. Ballard; Jon F. Dodd; James A. Sulikowski (Frontiers in Marine Science, 2024)
Pop-off satellite archival tags (PSATs) have been increasingly deployed on marine megafauna to remotely monitor their movements, behavior, and environmental preferences. These tags have also allowed the occasional novel documentation of ecological interactions, such as predation on tagged animals. A PSAT deployed on a pregnant porbeagle Lamna nasus in the Northwest Atlantic suggests the shark was predated upon in mesopelagic waters near Bermuda. Predation was evident approximately 5 months after tagging based on depth and temperature data transmitted by the PSAT. Four days prior to PSAT pop-off, depth data indicated that the tag continued to descend and ascend in the water column while the temperature remained approximately 5°C above ambient levels, even at several hundred meters in depth, indicating ingestion. Given the location of predation and elevated temperature at depth recorded by the pregnant porbeagle’s tag, potential predators include endothermic shark species such as the white shark Carcharodon carcharias and shortfin mako Isurus oxyrhinchus . This is the first evidence of predation on a porbeagle globally and provides novel insight into inter-specific interactions for this large, threatened shark species.

Drone-based photogrammetry reveals differences in humpback whale body condition and mass across North Atlantic foraging grounds - Chelsi Napoli; Nathan Hirtle; Julia Stepanuk; Fredrik Christiansen; Eleanor I. Heywood; Thomas J. Grove; Alyssa Stoller; Flordespina Dodds; Maria Glarou; Marianne H. Rasmussen; Gina L. Lonati; Kimberley T.A. Davies; et al. (Frontiers in Marine Science, 2024)
Baleen whales are key consumers in marine ecosystems and can serve as ecosystem sentinels. Body condition, defined as an individual’s energy stores relative to its structural size, can provide a useful proxy for health in baleen whales. As capital breeders, important life history events in baleen whales such as seasonal migrations and reproduction depend on having sufficient energy stores. Spatiotemporal variability of body condition of baleen whales can reflect differences in energy accumulated during the foraging season. Here we assess and compare the body condition and mass of humpback whales ( Megaptera novaeangliae) across four different foraging areas from the West Indies distinct population segment in the Northwest Atlantic. Morphometric measurements of humpback whales were obtained using unoccupied aerial systems (UAS, or drones) from the New York Bight, the Gulf of Maine, Iceland, and Greenland. Uncertainty in morphometric estimates was incorporated and propagated using a bootstrapping approach. Measurements were used to estimate body volume and calculate a body condition index (BCI) for each individual whale. Since body mass is a key parameter for understanding animal physiology and bioenergetics, we further compared whale body mass to body size between foraging areas by converting body volume to body mass using estimates of tissue density from tagging studies. BCI showed significant differences between foraging areas with a large effect size (ANCOVA: mean η 2 = 0.168; all p< 0.001) when incorporating day of year and year as covariates. Humpback whales in the Gulf of Maine showed significantly higher BCI than those in the New York Bight, Iceland, and Greenland. Standardized Major Axis (SMA) regressions comparing log-log relationships of both body volume and body mass, respectively, to total length reinforced these results. Humpback whales in the Gulf of Maine showed significantly higher elevation in the SMAs than those in the other study regions (p<0.001), implying that humpback whales foraging in the Gulf of Maine accumulated greater energy reserves for a given body size. Estimates of body mass indicate that for a given body length, humpback whales in the Gulf of Maine have an 18% greater body mass than those in the New York Bight, Iceland, or Greenland. Regional differences in prey availability or anthropogenic threats could contribute to the observed patterns in body condition. Our findings highlight the importance of regional environmental factors to the nutritional health of baleen whales.

The phylogenetic analysis of two invasive Trapa species in the United States revealed by chloroplast genomes and morphological traits - Xiang-Rong Fan; Nancy Rybicki; Lynde L. Dodd; Jie Min; Wei Li; Xiu-Ling Li; Godfrey Kinyori Wagutu; Yuan-Yuan Chen (Biological Invasions, 2024)

The special sauce of the Cancer Prevention and Control Research Network: 20 years of lessons learned in developing the evidence base, building community capacity, and translating research into practice - Stephanie B. Wheeler; Rebecca J. Lee; Alexa L. Young; Adam Dodd; Charlotte Ellis; Bryan J. Weiner; Kurt M. Ribisl; Prajakta Adsul; Sarah A. Birken; María E. Fernández; Peggy A. Hannon; James R. Hébert; et al. (Cancer Causes & Control, 2023)
Purpose The Cancer Prevention and Control Research Network (CPCRN) is a national network focused on accelerating the translation of cancer prevention and control research evidence into practice through collaborative, multicenter projects in partnership with diverse communities. From 2003 to 2022, the CPCRN included 613 members. Methods We: (1) characterize the extent and nature of collaborations through a bibliometric analysis of 20 years of Network publications; and (2) describe key features and functions of the CPCRN as related to organizational structure, productivity, impact, and focus on health equity, partnership development, and capacity building through analysis of 22 in-depth interviews and review of Network documentation. Results Searching Scopus for multicenter publications among the CPCRN members from their time of Network engagement yielded 1,074 collaborative publications involving two or more members. Both the overall number and content breadth of multicenter publications increased over time as the Network matured. Since 2004, members submitted 123 multicenter grant applications, of which 72 were funded (59%), totaling more than $77 million secured. Thematic analysis of interviews revealed that the CPCRN’s success—in terms of publication and grant productivity, as well as the breadth and depth of partnerships, subject matter expertise, and content area foci—is attributable to: (1) its people–the inclusion of members representing diverse content-area interests, multidisciplinary perspectives, and geographic contexts; (2) dedicated centralized structures and processes to enable and evaluate collaboration; and (3) focused attention to strategically adapting to change. Conclusion CPCRN’s history highlights organizational, strategic, and practical lessons learned over two decades to optimize Network collaboration for enhanced collective impact in cancer prevention and control. These insights may be useful to others seeking to leverage collaborative networks to address public health problems.

A narrative review of nutrient based indexes to assess diet quality and the proposed total nutrient index that reflects total dietary exposures - Alexandra E. Cowan; Shinyoung Jun; Janet A. Tooze; Kevin W. Dodd; Jaime J. Gahche; Heather A. Eicher-Miller; Patricia M. Guenther; Johanna T. Dwyer; Nancy Potischman; Anindya Bhadra; Raymond J. Carroll; Regan L. Bailey (Critical Reviews in Food Science and Nutrition, 2023)

Impacts of Riparian and Non-riparian Woody Encroachment on Tallgrass Prairie Ecohydrology - Rachel M. Keen; Jesse B. Nippert; Pamela L. Sullivan; Zak Ratajczak; Brynn Ritchey; Kimberly O’Keefe; Walter K. Dodds (Ecosystems, 2023)

Resilience of ecosystem service delivery in grasslands in response to single and compound extreme weather events - Rosalind J. Dodd; David R. Chadwick; Paul W. Hill; Felicity Hayes; Antonio R. Sánchez-Rodríguez; Dylan Gwynn-Jones; Simon M. Smart; Davey L. Jones (Science of The Total Environment, 2023)

Front-Loaded Versus Low-Intermittent Phenobarbital Dosing for Benzodiazepine-Resistant Severe Alcohol Withdrawal Syndrome - Poorvi Shah; Kati L. Stegner-Smith; Mohamad Rachid; Tabassum Hanif; Kenneth W. Dodd (Journal of Medical Toxicology, 2022)

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Green Nourishment: An Innovative Nature-Based Solution for Coastal Erosion - Wen L. Chen; Peter Muller; Robert C. Grabowski; Nicholas Dodd (Frontiers in Marine Science, 2022)
Coastal erosion poses an urgent threat to life and property in low-lying regions. Sand nourishment is increasingly used as a nature-based solution but requires significant natural resources and replenishment over time. In this study, a novel form of nourishment is explored that combines shoreface nourishment and seagrass restoration to mitigate coastal erosion (i.e., green nourishment). Using the coastal morphodynamic model Xbeach, the impact of seagrass planting on wave energy dissipation, sediment erosion and transport, and morphological evolution of a cross-shore profile was studied for mild wave conditions and an intense storm. Model results indicate that a seagrass meadow enhances the wave energy dissipation provided by a shoreface nourishment, and suggests that it may be particularly effective in sediment transport mitigation when implemented in a sheltered nearshore area. The shoreface nourishment reduced the wave height on the seagrass meadow, and reduced the rate of seagrass destruction by deposition or erosion above the grass height after the storm event. Green nourishment also reduced beach foreshore erosion caused by a simulated storm event. An alternative, more cost-effective planting technique using seagrass seeds was explored, which showed similar coastal erosion protection benefits for seagrass transplants. This modeling study found that green nourishment is potentially an effective nature-based solution for coastal erosion and flooding on sandy coasts, and future studies are recommended to evaluate its morphological, ecological and flood risk reduction benefits in the field.

One beach amongst many: how weak fidelity to a focal nesting site can bias demographic rates in marine turtles - Joseph B. Pfaller; Sara M. Weaver; Kristina L. Williams; Mark G. Dodd; Matthew H. Godfrey; DuBose B. Griffin; S. Michelle Pate; C. George Glen; Campbell J. Nairn; Brian M. Shamblin (Marine Biology, 2022)

Shifting stoichiometry: Long‐term trends in stream‐dissolved organic matter reveal altered C:N ratios due to history of atmospheric acid deposition - Bianca M. Rodríguez‐Cardona; Adam S. Wymore; Alba Argerich; Rebecca T. Barnes; Susana Bernal; E. N. Jack Brookshire; Ashley A. Coble; Walter K. Dodds; Hannah M. Fazekas; Ashley M. Helton; Penny J. Johnes; Sherri L. Johnson; et al. (Global Change Biology, 2022)
Dissolved organic carbon (DOC) and nitrogen (DON) are important energy and nutrient sources for aquatic ecosystems. In many northern temperate, freshwater systems DOC has increased in the past 50 years. Less is known about how changes in DOC may vary across latitudes, and whether changes in DON track those of DOC. Here, we present long‐term DOC and DON data from 74 streams distributed across seven sites in biomes ranging from the tropics to northern boreal forests with varying histories of atmospheric acid deposition. For each stream, we examined the temporal trends of DOC and DON concentrations and DOC:DON molar ratios. While some sites displayed consistent positive or negative trends in stream DOC and DON concentrations, changes in direction or magnitude were inconsistent at regional or local scales. DON trends did not always track those of DOC, though DOC:DON ratios increased over time for ~30% of streams. Our results indicate that the dissolved organic matter (DOM) pool is experiencing fundamental changes due to the recovery from atmospheric acid deposition. Changes in DOC:DON stoichiometry point to a shifting energy‐nutrient balance in many aquatic ecosystems. Sustained changes in the character of DOM can have major implications for stream metabolism, biogeochemical processes, food webs, and drinking water quality (including disinfection by‐products). Understanding regional and global variation in DOC and DON concentrations is important for developing realistic models and watershed management protocols to effectively target mitigation efforts aimed at bringing DOM flux and nutrient enrichment under control.

Health system resilience to extreme weather events in Asia-Pacific: a scoping review - Vinussa Rameshshanker; Sara Wyngaarden; Lincoln L. Lau; Warren Dodd (Climate and Development, 2021)

Exploring genetic diversity of lowland avocado (Persea americana Mill.) as a genetic reservoir for breeding - Eduardo Sandoval-Castro; Ayesha Y. Peraza-Magallanes; Richard S. Dodd; Vanessa E. T. M. Ashworth; Abraham Cruz-Mendívil; Carlos L. Calderón-Vázquez (Genetic Resources and Crop Evolution, 2021)

Tidal Marsh Restoration Optimism in a Changing Climate and Urbanizing Seascape - Nathan J. Waltham; Caitlin Alcott; Myriam A. Barbeau; Just Cebrian; Rod M. Connolly; Linda A. Deegan; Kate Dodds; Lucy A. Goodridge Gaines; Ben L. Gilby; Christopher J. Henderson; Catherine M. McLuckie; Thomas J. Minello; et al. (Estuaries and Coasts, 2021)

Encapsulating Polyethyleneimine-DNA Nanoplexes into PEGylated Biodegradable Microparticles Increases Transgene Expression In Vitro and Reduces Inflammatory Responses In Vivo - Treniece L. Terry; Brittany E. Givens; Andrea Adamcakova-Dodd; Peter S. Thorne; Victor G. J. Rodgers; Aliasger K. Salem (AAPS PharmSciTech, 2021)

In search of the “missing majority” of nesting loggerhead turtles: improved inter-seasonal recapture rates through subpopulation-scale genetic tagging - Brian M. Shamblin; Mark G. Dodd; S. Michelle Pate; Matthew H. Godfrey; Joseph B. Pfaller; Kristina L. Williams; Breanna L. Ondich; David A. Steen; Elizabeth S. Darrow; Paul Hillbrand; Ruth Boettcher; Michael S. Coyne; et al. (Marine Biology, 2021)

Spatial co‐localisation of extreme weather events: a clear and present danger - Rosalind J. Dodd; David R. Chadwick; Ian M. Harris; Adrian Hines; Dan Hollis; Theodoros Economou; Dylan Gwynn‐Jones; John Scullion; David A. Robinson; David L. Jones (Ecology Letters, 2021)
Extreme weather events have become a dominant feature of the narrative surrounding changes in global climate with large impacts on ecosystem stability, functioning and resilience; however, understanding of their risk of co‐occurrence at the regional scale is lacking. Based on the UK Met Office’s long‐term temperature and rainfall records, we present the first evidence demonstrating significant increases in the magnitude, direction of change and spatial co‐localisation of extreme weather events since 1961. Combining this new understanding with land‐use data sets allowed us to assess the likely consequences on future agricultural production and conservation priority areas. All land‐uses are impacted by the increasing risk of at least one extreme event and conservation areas were identified as the hotspots of risk for the co‐occurrence of multiple event types. Our findings provide a basis to regionally guide land‐use optimisation, land management practices and regulatory actions preserving ecosystem services against multiple climate threats.

Predators, Disease, and Environmental Change in the Nearshore Ecosystem: Mortality in Southern Sea Otters (Enhydra lutris nereis) From 1998–2012 - Melissa A. Miller; Megan E. Moriarty; Laird Henkel; Martin Tim Tinker; Tristan L. Burgess; Francesca I. Batac; Erin Dodd; Colleen Young; Michael D. Harris; David A. Jessup; Jack Ames; Patricia A. Conrad; et al. (Frontiers in Marine Science, 2020)
We compiled findings from 15 years (1998–2012) of southern sea otter ( Enhydra lutris nereis ) necropsies, incorporating data from 560 animals. Sensitive diagnostic tests were used to detect biotoxins, bacteria, parasites and fungi. Methods to classify primary and contributing causes of death (COD) and sequelae utilized an updated understanding of health risks affecting this population. Several interesting patterns emerged, including identification of coastal regions of high mortality risk for sea otter mortality due to shark bite, cardiomyopathy, toxoplasmosis, sarcocystosis, acanthocephalan peritonitis and coccidioidomycosis. We identified demographic attributes that enhanced the risk of disease in relation to age, sex, and reproductive stage. Death due to white shark ( Carcharodon carcharias ) bite increased dramatically during the study period and was the most common primary COD. However, when primary and contributing COD were combined, the most prevalent COD was infectious disease (affecting 63% of otters), especially fatal infections by acanthocephalans ( Profilicollis spp.) and protozoa (e.g., Sarcocystis neurona and Toxoplasma gondii ). Fatal bacterial infections were also extremely common as a primary process or a sequela, affecting 68% of examined otters. Substantial advances were made in identifying sea otters that died following exposure to the pervasive marine neurotoxin domoic acid (DA), and DA intoxication was conservatively estimated as a primary or contributing COD for 20% of otters. Cardiomyopathy was also highly prevalent as a primary or contributing COD (41%) and exhibited significant associations with DA intoxication and protozoal infection. For adult and aged adult females in late pup care through post-weaning at the time of death, 83% had end lactation syndrome (ELS) as a primary or contributing COD. This comprehensive longitudinal dataset is unique in its depth and scope. The large sample size and extensive time period provided an opportunity to investigate mortality patterns in a changing environment and identify spatial and temporal disease “hot spots” and emerging threats. Our findings will help improve estimates of population-level impacts of specific threats and optimize conservation and environmental mitigation efforts for this threatened species.

Timing of oviposition influences the effects of a non-native grass on amphibian development - Chelsea S. Kross; Allyn K. Dodd; Philip L. Mariage; John D. Willson (Oecologia, 2020)

Regional environmental variation and local species interactions influence biogeographic structure on oyster reefs - Jonathan H. Grabowski; Tarik C. Gouhier; James E. Byers; Luke F. Dodd; A. Randall Hughes; Michael F. Piehler; David L. Kimbro (Ecology, 2020)
Although species interactions are often assumed to be strongest at small spatial scales, they can interact with regional environmental factors to modify food web dynamics across biogeographic scales. The eastern oyster ( Crassostrea virginica ) is a widespread foundational species of both ecological and economic importance. The oyster and its associated assemblage of fish and macroinvertebrates is an ideal system to investigate how regional differences in environmental variables influence trophic interactions and food web structure. We quantified multiple environmental factors, oyster reef properties, associated species, and trophic guilds on intertidal oyster reefs within 10 estuaries along 900 km of the southeastern United States. Geographical gradients in fall water temperature and mean water depth likely influenced regional (i.e., the northern, central and southern sections of the SAB) variation in oyster reef food web structure. Variation in the biomass of mud crabs, an intermediate predator, was mostly (84.1%) explained by reefs within each site, and did not differ substantially among regions; however, regional variation in the biomass of top predators and of juvenile oysters also contributed to biogeographic variation in food web structure. In particular, region explained almost half (40.2%) of the variation in biomass of predators of blue crab, a top predator that was prevalent only in the central region where water depth was greater. Field experiments revealed that oyster mortality due to predation was greatest in the central region, suggesting spatial variation in the importance of trophic cascades. However, high oyster recruitment in the middle region probably compensates for this enhanced predation, potentially explaining why relatively less variation (17.9%) in oyster cluster biomass was explained by region. Region also explained over half of the variation in biomass of mud crab predators (55.2%), with the southern region containing almost an order of magnitude more biomass than the other two regions. In this region, higher water temperatures in the fall corresponded with higher biomass of fish that consume mud crabs and of fish that consume juvenile and forage fish, whereas biomas of their prey (mud crabs and juvenile and forage fish, respectively) was generally low in the southern region. Collectively, these results show how environmental gradients interact with trophic cascades to structure food webs associated with foundation species across biogeographic regions.

Algae and Clay Water Additives Differentially Impact Survival and Microbial Community Structure in Sablefish (Anoplopoma fimbria) Rearing Tanks - Melissa L. Pierce; Jonathan S. F. Lee; Emily Dodd; Rachel S. Poretsky (Frontiers in Marine Science, 2019)

A mechanistic cohort study evaluating cognitive impairment in women treated for breast cancer - Janette L. Vardy; Myrle M. Stouten-Kemperman; Gregory Pond; Christopher M. Booth; Sean B. Rourke; Haryana M. Dhillon; Anna Dodd; Adrian Crawley; Ian F. Tannock (Brain Imaging and Behavior, 2019)

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Improved female abundance and reproductive parameter estimates through subpopulation-scale genetic capture-recapture of loggerhead turtles - Brian M. Shamblin; Mark G. Dodd; DuBose B. Griffin; S. Michelle Pate; Matthew H. Godfrey; Michael S. Coyne; Kristina L. Williams; Joseph B. Pfaller; Breanna L. Ondich; Kimberly M. Andrews; Ruth Boettcher; Campbell J. Nairn (Marine Biology, 2017)

Take-all decline in New Zealand wheat soils and the microorganisms associated with the potential mechanisms of disease suppression - Soonie Chng; Matthew G. Cromey; Sarah L. Dodd; Alison Stewart; Ruth C. Butler; Marlene V. Jaspers (Plant and Soil, 2015)

Effects of climate change on the delivery of soil‐mediated ecosystem services within the primary sector in temperate ecosystems: a review and New Zealand case study - Kate H. Orwin; Bryan A. Stevenson; Simeon J. Smaill; Miko U. F. Kirschbaum; Ian A. Dickie; Brent E. Clothier; Loretta G. Garrett; Tony J. van der Weerden; Michael H. Beare; Denis Curtin; Cecile A. M. de Klein; Michael B. Dodd; et al. (Global Change Biology, 2015)
Future human well‐being under climate change depends on the ongoing delivery of food, fibre and wood from the land‐based primary sector. The ability to deliver these provisioning services depends on soil‐based ecosystem services (e.g. carbon, nutrient and water cycling and storage), yet we lack an in‐depth understanding of the likely response of soil‐based ecosystem services to climate change. We review the current knowledge on this topic for temperate ecosystems, focusing on mechanisms that are likely to underpin differences in climate change responses between four primary sector systems: cropping, intensive grazing, extensive grazing and plantation forestry. We then illustrate how our findings can be applied to assess service delivery under climate change in a specific region, using New Zealand as an example system. Differences in the climate change responses of carbon and nutrient‐related services between systems will largely be driven by whether they are reliant on externally added or internally cycled nutrients, the extent to which plant communities could influence responses, and variation in vulnerability to erosion. The ability of soils to regulate water under climate change will mostly be driven by changes in rainfall, but can be influenced by different primary sector systems' vulnerability to soil water repellency and differences in evapotranspiration rates. These changes in regulating services resulted in different potentials for increased biomass production across systems, with intensively managed systems being the most likely to benefit from climate change. Quantitative prediction of net effects of climate change on soil ecosystem services remains a challenge, in part due to knowledge gaps, but also due to the complex interactions between different aspects of climate change. Despite this challenge, it is critical to gain the information required to make such predictions as robust as possible given the fundamental role of soils in supporting human well‐being.

Evaluating the landscape of fear between apex predatory sharks and mobile sea turtles across a large dynamic seascape - Neil Hammerschlag; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark Dodd; Michael G. Frick; Matthew H. Godfrey; Brendan J. Godley; DuBose B. Griffin; Kyra Hartog; Sally R. Murphy; Thomas M. Murphy; et al. (Ecology, 2015)
The “landscape of fear” model has been proposed as a unifying concept in ecology, describing, in part, how animals behave and move about in their environment. The basic model predicts that as an animal's landscape changes from low to high risk of predation, prey species will alter their behavior to risk avoidance. However, studies investigating and evaluating the landscape of fear model across large spatial scales (tens to hundreds of thousands of square kilometers) in dynamic, open, aquatic systems involving apex predators and highly mobile prey are lacking. To address this knowledge gap, we investigated predator–prey relationships between tiger sharks ( Galeocerdo cuvier ) and loggerhead turtles ( Caretta caretta ) in the North Atlantic Ocean. This included the use of satellite tracking to examine shark and turtle distributions as well as their surfacing behaviors under varying levels of home range overlap. Our findings revealed patterns that deviated from our a priori predictions based on the landscape of fear model. Specifically, turtles did not alter their surfacing behaviors to risk avoidance when overlap in shark–turtle core home range was high. However, in areas of high overlap with turtles, sharks exhibited modified surfacing behaviors that may enhance predation opportunity. We suggest that turtles may be an important factor in determining shark distribution, whereas for turtles, other life history trade‐offs may play a larger role in defining their habitat use. We propose that these findings are a result of both biotic and physically driven factors that independently or synergistically affect predator–prey interactions in this system. These results have implications for evolutionary biology, community ecology, and wildlife conservation. Further, given the difficulty in studying highly migratory marine species, our approach and conclusions may be applied to the study of other predator–prey systems.

A double-blind, placebo-controlled study evaluating the effects of caffeine and L-theanine both alone and in combination on cerebral blood flow, cognition and mood - F. L. Dodd; D. O. Kennedy; L. M. Riby; C. F. Haskell-Ramsay (Psychopharmacology, 2015)

The effect of impedance to root growth on plant architecture in wheat - Kemo Jin; Jianbo Shen; Rhys W. Ashton; Rodger P. White; Ian C. Dodd; Andrew L. Phillips; Martin A. J. Parry; William R. Whalley (Plant and Soil, 2015)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Factors affecting the foraging behaviour of the European shag: implications for seabird tracking studies - L. M. Soanes; J. P. Y. Arnould; S. G. Dodd; G. Milligan; J. A. Green (Marine Biology, 2014)

Use of the silverleaf fungus Chondrostereum purpureum for biological control of stump-sprouting, riparian weedy tree species in New Zealand - S. E. Bellgard; V. W. Johnson; D. J. Than; N. Anand; C. J. Winks; G. Ezeta; S. L. Dodd (Australasian Plant Pathology, 2014)

Non-target impacts of the biocontrol agent Trichoderma atroviride on plant health and soil microbial communities in two native ecosystems in New Zealand - K. L. McLean; S. L. Dodd; R. F. Minchin; M. Ohkura; D. Bienkowski; A. Stewart (Australasian Plant Pathology, 2014)

Foraging habitats and migration corridors utilized by a recovering subpopulation of adult female loggerhead sea turtles: implications for conservation - DuBose B. Griffin; Sally R. Murphy; Michael G. Frick; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark G. Dodd; Matthew H. Godfrey; Brendan J. Godley; Lucy A. Hawkes; Thomas M. Murphy; Kristina L. Williams; et al. (Marine Biology, 2013)

Genotypic variation in the ability of wheat roots to penetrate wax layers - W. R. Whalley; I. C. Dodd; C. W. Watts; C. P. Webster; A. L. Phillips; J. Andralojc; R. P. White; W. J. Davies; M. A. J. Parry (Plant and Soil, 2013)

Effects of different rates of Gaeumannomyces graminis var. tritici inoculum for detecting take-all suppression in soils - S. F. Chng; A. Stewart; M. G. Cromey; S. L. Dodd; R. C. Butler; M. V. Jaspers (Australasian Plant Pathology, 2013)

Relationships among biomarkers of one-carbon metabolism - Will D. King; Vikki Ho; Linda Dodds; Sherry L. Perkins; R. Ian Casson; Thomas E. Massey (Molecular Biology Reports, 2012)

Genetic structure of the southeastern United States loggerhead turtle nesting aggregation: evidence of additional structure within the peninsular Florida recovery unit - Brian M. Shamblin; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Anton D. Tucker; Chris Johnson; Raymond R. Carthy; Russell A. Scarpino; Erin McMichael; David S. Addison; Kristina L. Williams; Michael G. Frick; et al. (Marine Biology, 2011)

PCR primers to distinguish Armillaria species found in New Zealand - S. L. Dodd; T. D. Ramsfield; J. W. Marshall (Australasian Plant Pathology, 2010)

De novo synthesis of human dermis in vitro in the absence of a three-dimensional scaffold - Tara Pouyani; Vincent Ronfard; Paul G. Scott; Carole M. Dodd; Aftab Ahmed; Richard L. Gallo; Nancy L. Parenteau (In Vitro Cellular & Developmental Biology - Animal, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Different native arbuscular mycorrhizal fungi influence the coexistence of two plant species in a highly alkaline anthropogenic sediment - Rui S. Oliveira; Paula M. L. Castro; John C. Dodd; Miroslav Vosátka (Plant and Soil, 2006)

Studies on the diversity of arbuscular mycorrhizal fungi and the efficacy of two native isolates in a highly alkaline anthropogenic sediment - R. S. Oliveira; M. Vosátka; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2005)

Differential expression of the GABA transporters GAT-1 and GAT-3 in brains of rats, cats, monkeys and humans - David V. Pow; Robert K. P. Sullivan; Susan M. Williams; Heather L. Scott; Peter R. Dodd; David Finkelstein (Cell and Tissue Research, 2005)

Rapid screening of invertebrate predators for multiple prey DNA targets - G. L. HARPER; R. A. KING; C. S. DODD; J. D. HARWOOD; D. M. GLEN; M. W. BRUFORD; W. O. C. SYMONDSON (Molecular Ecology, 2005)
DNA‐based techniques are providing valuable new approaches to tracking predator–prey interactions. The gut contents of invertebrate predators can be analysed using species‐specific primers to amplify prey DNA to confirm trophic links. The problem is that each predator needs to be analysed with primers for the tens of potential prey available at a field site, even though the mean number of species detected in each gut may be as few as one or two. Conducting all these PCRs (polymerase chain reactions) is a lengthy process, and effectively precludes the analysis of the hundreds of predators that might be required for a meaningful ecological study. We report a rapid, more sensitive and practical approach. Multiplex PCRs, incorporating fluorescent markers, were found to be effective at amplifying degraded DNA from predators’ guts and could amplify mitochondrial DNA fragments from 10+ species simultaneously without ‘drop outs’. The combined PCR products were then separated by size on polyacrylamide gels on an ABI377 sequencer. New primers to detect the remains of aphids, earthworms, weevils and molluscs in the guts of carabid predators were developed and characterized. The multiplex‐sequencer approach was then applied to field‐caught beetles, some of which contained DNA from as many as four different prey at once. The main prey detected in the beetles proved to be earthworms and molluscs, although aphids and weevils were also consumed. The potential of this system for use in food‐web research is discussed.

The role of group I metabotropic glutamate receptors in neuronal excitotoxicity in alzheimer’s disease - Vicky W. -W. Tsai; Heather L. Scott; Richard J. Lewis; Peter R. Dodd (Neurotoxicity Research, 2005)

Natal homing in juvenile loggerhead turtles ( Caretta caretta ) - BRIAN W. BOWEN; ANNA L. BASS; SHAIO‐MEI CHOW; MEREDITH BOSTROM; KAREN A. BJORNDAL; ALAN B. BOLTEN; TOSHINORI OKUYAMA; BENJAMIN M. BOLKER; SHERYAN EPPERLY; ERIN LACASELLA; DONNA SHAVER; MARK DODD; et al. (Molecular Ecology, 2004)
Juvenile loggerhead turtles ( Caretta caretta ) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences ( N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea ( N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (Φ ST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R 2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.

Carbon and nitrogen stoichiometry and nitrogen cycling rates in streams - Walter K. Dodds; Eugenia Martí; Jennifer L. Tank; Jeffrey Pontius; Stephen K. Hamilton; Nancy B. Grimm; William B. Bowden; William H. McDowell; Bruce J. Peterson; H. Maurice Valett; Jackson R. Webster; Stan Gregory (Oecologia, 2004)

Monitoring the survival and spread of the biocontrol fungus Trichoderma atroviride (C65) on kiwifruit using a molecular marker - S. L. Dodd; R. A. Hill; A. Stewart (Australasian Plant Pathology, 2004)

Hierarchical genetic structure in fragmented populations of the Little Pocket Mouse (Perognathus longimembris) in Southern California - Andrea Swei; Philip V. Brylski; Wayne D. Spencer; Shana C. Dodd; James L. Patton (Conservation Genetics, 2003)

Taxonomy and phylogenetic relationships of two species of Hypocrea with Trichoderma anamorphs - Sarah L. Dodd; Elke Lieckfeldt; Priscila Chaverri; Barrie E. Overton; Gary J. Samuels (Mycological Progress, 2002)

Interaction of blood flow and oxygen delivery affects peak $$\dot V{\rm O}_2 $$ and fatigue in canine muscle in situ - Ioannis S. Vrabas; Stephen L. Dodd; Pat M. Crawford (European Journal of Applied Physiology, 2002)

The mycorrhizal status of Phragmites australis in several polluted soils and sediments of an industrialised region of Northern Portugal - R.S. Oliveira; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2001)

Mycelium of Arbuscular Mycorrhizal fungi (AMF) from different genera: form, function and detection - John C. Dodd; Claire L. Boddington; Alia Rodriguez; Carmen Gonzalez-Chavez; Irdika Mansur (Plant and Soil, 2000)

Hydrodynamic properties of mucins secreted by primary cultures of Guinea-pig tracheal epithelial cells: determination of diffusion coefficients by analytical ultracentrifugation and kinetic analysis of mucus gel hydration and dissolution - Sara Dodd; Graham A. Place; R. L. Hall; Stephen E. Harding (European Biophysics Journal, 1998)

A comparison of the development and metabolic activity of mycorrhizas formed by arbuscular mycorrhizal fungi from different genera on two tropical forage legumes - C. L. Boddington; J. C. Dodd (Mycorrhiza, 1998)